PENDAMPINGAN DAN PENYUSUNAN ARGUMENTASI UNTUK KEPERLUAN LOMBA DEBAT DI SMA NEGERI 17 JAKARTA - Adhari, Ade; Ongaran , Joshua Steven (Jurnal Serina Abdimas, 2024)
SMA Negeri 17 Jakarta is one of the public high schools located in Jakarta, Indonesia. The school is known as an educational institution that has a strong commitment to the academic, character and skill development of students. With adequate facilities and qualified teaching staff, SMA Negeri 17 Jakarta strives to create a conducive learning environment for its students. The PKM team of Tarumanegara University has a program, one of which is mentoring and preparing arguments for the debate competition. This program was carried out with the aim of honing students' abilities in debate and providing an understanding of debate techniques, preparation of strong arguments, debate structure, and public speaking techniques. This program was implemented using two methods, namely the lecture method and the focus group discussion method. The lecture method was carried out with the aim of providing basic material on debate techniques, preparation of strong arguments, debate structure, and public speaking techniques. The material provided includes basic debate theories, examples of debate cases, and strategies for winning debates. While the focus group discussion method was carried out with the aim of exploring students' understanding of the material that had been delivered previously. This program went well as shown by the results of this activity which showed an increase in student understanding by 70% after attending the program, as well as active participation in discussions which showed the development of students' abilities in compiling debate arguments and public speaking skills. ABSTRAK SMA Negeri 17 Jakarta adalah salah satu sekolah menengah atas negeri yang terletak di Jakarta, Indonesia. Sekolah ini dikenal sebagai institusi pendidikan yang memiliki komitmen kuat terhadap pengembangan akademik, karakter, dan keterampilan siswa. Dengan fasilitas yang memadai dan staf pengajar berkualitas, SMA Negeri 17 Jakarta berusaha untuk menciptakan lingkungan belajar yang kondusif bagi siswanya. Tim PKM Universitas Tarumanegara memiliki program, salah satunya pendampingan dan penyusunan argumentasi untuk keperluan lomba debat. Program ini dilaksanakan dengan tujuan untuk mengasah kemampuan siswa dalam debat dan memberikan pemahaman mengenai teknik debat, penyusunan argumentasi yang kuat, struktur debat, serta teknik public speaking. Program ini dilaksanakan dengan dua metode yakni metode ceramah dan metode focus froup discussion. Metode ceramah dilakukan dengan tujuan untuk memberikan materi dasar tentang teknik debat, penyusunan argumentasi yang kuat, struktur debat, serta teknik public speaking. Materi yang diberikan meliputi teori-teori dasar debat, contoh kasus debat, serta strategi memenangkan debat. Sedangkan metode focus group discussion dilaksanakan dengan tujuan untuk menggali pemahaman siswa mengenai materi yang sudah disampaikan sebelumnya. Program ini berjalan lancar ditunjukkan dengan hasil kegiatan ini menunjukkan peningkatan pemahaman siswa sebesar 70% setelah mengikuti program, serta partisipasi aktif dalam diskusi yang menunjukkan perkembangan kemampuan siswa dalam menyusun argumentasi debat dan kemampuan public speaking.